Fetal akinesia deformation sequence due to a congenital disorder of glycosylation. (31st May 2015) - Ganetzky, Rebecca; Izumi, Kosuke; Edmondson, Andrew; Muraresku, Colleen Clarke; Zackai, Elaine; Deardorff, Matthew; Ganesh, Jaya
<x xml:space="preserve">Abstract</x> Congenital disorders of Glycosylation (CDG) are increasingly emerging as a major underlying etiology for patients with complex neurogenetic malformations and dysmorphic features. We describe a newborn female with arthrogryposis multiplex due to fetal akinesia secondary to CDG‐DPAGT1. Pregnancy was complicated by reduced fetal movements. At birth, the patient was evaluated for intrauterine growth restriction, bilateral cataracts, and multiple joint contractures. She had markedly reduced spontaneous movements, hypotonia, weak cry, and poor suck. She had ventilator‐dependent central respiratory depression. Brain MRI showed delayed myelination and an incomplete cerebellar vermis. Transferrin isoelectric focusing was suggestive of a type I congenital disorder of glycosylation. Sequencing revealed a homozygous missense mutation in dolichyl‐phosphate N‐acetylglucosaminephosphotransferase (DPAGT1), exon 3, p.Leu118Val, consistent with DPAGT1‐CDG. There have been seventeen previously reported cases of DPAGT1‐CDG, including two similar cases with multiple contractures. This case highlights the importance of considering congenital disorders of glycosylation in the differential diagnosis for arthrogryposis. © 2015 Wiley Periodicals, Inc.